13 A CT coronary angiography first strategy in patients determined to have an indication for invasive coronary angiogram: a meta-analysis. (6th October 2022) - Murphy, G; Naughton, A; Murphy, R; McCaughey, C; Maree, A
Abstract : Introduction: Invasive coronary angiogram (ICA) is the gold standard for the diagnosis and treatment of cardiac chest pain; however, there are associated risks. Furthermore, over one million ICAs in Europe each year do not progress to intervention. The application of CT Coronary angiography (CTCA) as a gatekeeper for those with an indication for a coronary angiogram is an attractive non-invasive alternative that could reduce non-interventional ICA. This metanalysis aims to identify high-quality randomised controlled trials comparing a CTCA first approach in patients with an indication for ICA. Methods: A comprehensive search of Medline, Embase and PubMed was performed for randomised controlled trials comparing direct to ICA or CTCA first for stable patients with an established indication for ICA regardless of pre-test risk. Two independent reviewers completed the search that yielded 1908 results, 1672 after duplicates were removed. Of these, 186 were selected for abstract review and 42 for full-text review. Trials were included if they were randomised control trials, reporting clinical outcomes and included patients with an indication for ICA. Studies were excluded if they necessitated any functional test before randomisation, compared multiple imaging modalities, were not eligible for ICA or if they included patients with possible acute coronary syndrome. The four included randomised trials were Discharge, CAT-CAD, Conserve and CADMAN. Primary outcomes were the rate of PCI and CABG. Secondary safety outcomes included MACE, diagnosis of obstructive disease and bail-out ICA in those originally randomised to the CTCA group. Results: Meta-analysis of the randomised trials demonstrated a significant decrease in PCI (OR 0.72 95% CI [0.62, 0.89]) and CABG rates (OR 0.6 95% CI [0.42, 0.85]) with a CTCA first approach. There was no significant difference in the rates of MACE (OR 0.83 [0.61, 1.12]) with numerically fewer events in the CTCA arm. There was no difference in obstructive coronary artery disease rates between the two arms. Rates of a subsequent ICA in the CTCA group were 8.6% (244/2819) Vs 98% (2645/2694) in the ICA group ( figure 1 ). Conclusion: This meta-analysis of 5613 patients with an indication for an ICA demonstrates a significant reduction in rates of PCI and CABG when managed with a CTCA first approach. There was no significant difference in rates of MACE between the two approaches. A CTCA first approach may represent a less invasive first-line diagnostic technique for many patients.